PATHOMORPHOLOGY OF CERVICAL INTRAEPITHELIAL NEOPLASIA IN WOMEN WITH INFERTILITY - Kindrativ, E.O.; Henyk, N.I. (World of Medicine and Biology, 2021)
The article presents the pathomorphological features of cervical intraepithelial neoplasia in women with infertility. Cervical biopsy specimens of 250 women were studied. All cases were divided into two groups, differing in papillomavirus infection presence. The patients with tubal, hormonal and combined forms of infertility represent the risk group for the development and progression of papillomavirus infection associated cervical intraepithelial neoplasia. The reduction in the thickness of non-keratinized stratified squamous epithelium to bulk density index of capillaries of the cervix mucous membrane was observed upon increase of cervical intraepithelial neoplasia severity. The regression equation of the dependence of these parameters was defined. This morphological feature may indicate an early stage of tumour development and can be used as an additional criterion for differential diagnosis of cervical intraepithelial neoplasia severity.